Formulation and Analysis of Handwritten Batik Wax Quality from Recycled Materials - Dodi Rahmad; Muhammad Kusumawan Herliansyah; Andi Sudiarso; Agus Haerudin (Performa: Media Ilmiah Teknik Industri, 2024)
Used cooking oil can be utilized as an alternative raw material for making batik wax. Recycling batik wax involves using recycled materials such as used wax, used cooking oil, and other substances like paraffin, microwax, colophonium resin, and damar resin. The recycling of used wax and the utilization of used cooking oil are crucial for the batik industry as they reduce production costs and environmental pollution. A combination of Taguchi and Grey Relational Analysis (GRA) method is employed to obtain optimal values for the response characteristics of line width continuity and permeability of wax. Recycled and new wax is applied to mori fabric and compared based on batik quality criteria. The research results indicate that the optimal composition for recycled wax consists of 510 grams of used wax (41.5%), 36 grams of used cooking oil (2.9%), 102 grams of paraffin (9.8%), 84 grams of microwax (6.8%), 300 grams of colophonium resin (24.4%), and 180 grams of damar resin (14.6%). According to batik experts' assessments, the quality of recycled batik wax is equivalent to that of new batik wax. Recycled batik wax has the melting point of 67.9 °C, the viscosity value of 90.15 cP, and the production cost of Rp 30.909,00.